Frontispiece: Discovery of Structural Complexity through Self‐Assembly of Molecules Containing Rodlike Components. Issue 30 (27th May 2020) - Zhang, Ruimeng; Su, Zebin; Yan, Xiao‐Yun; Huang, Jiahao; Shan, Wenpeng; Dong, Xue‐Hui; Feng, Xueyan; Lin, Zhiwei; Cheng, Stephen Z. D.
Abstract : Self‐assembly is a process in which a disordered system spontaneously develops ordered structures without external directions. In materials science and technology, self‐assembly in the bulk has been extensively utilized to fabricate desired microscopic structures. Rodlike molecules have emerged as one of the most promising molecular building blocks to construct functional materials. Although the self‐assembly of conventional molecules containing rodlike components generally results in nematic or layered smectic phases, extensive efforts have revealed that rational molecular design provides a versatile platform to engineer rich self‐assembled structures. In their Review article on page 6741 ff., Feng, Lin and Cheng et al. summarize the first successes achieved in polyphilic liquid crystals and rod–coil block systems. Special attention is paid to recent progress in the conjugation of rodlike building blocks with other molecular building blocks through the molecular Lego approach.